2021
DOI: 10.1042/bsr20204099
|View full text |Cite
|
Sign up to set email alerts
|

SNHG15 knockdown inhibits diabetic nephropathy progression in pediatric patients by regulating the miR-141/ICAM-1 axisin vitro

Abstract: Long non-coding RNAs (lncRNAs) are confirmed to be involved in modulating diabetic nephropathy (DN). The present study is aimed to explore the regulatory mechanism of lncRNA small nucleolar RNA host gene 15 (SNHG15) on pediatric DN. Human glomerular mesangial cells (HGMCs) were exposed to high glucose (HG) to produce an in vitro model. The results showed that SNHG15 was remarkably up-regulated in pediatric DN tissues and HG-induced HGMCs. Functional experiments indicated that both silencing of SNHG15 and overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, the functions of many lncRNAs in gout have not been elucidated. We performed polymerase chain reaction (PCR) analysis on foot pad of gouty mice and sham mice to determine expression profiles of small nucleolar RNA host gene (SNHG) family members including SNHG1 [ 13 ], SNHG4 [ 14 ], SNHG5 [ 15 ], SNHG7 [ 16 ], SNHG8 [ 17 ], SNHG12 [ 18 ], SNHG14 [ 19 ], SNHG15 [ 20 ], SNHG16 [ 21 ] that were previously reported to regulate inflammatory response. The experimental results revealed that SNHG8 showed the most significant upregulation in gouty mice compared to sham mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functions of many lncRNAs in gout have not been elucidated. We performed polymerase chain reaction (PCR) analysis on foot pad of gouty mice and sham mice to determine expression profiles of small nucleolar RNA host gene (SNHG) family members including SNHG1 [ 13 ], SNHG4 [ 14 ], SNHG5 [ 15 ], SNHG7 [ 16 ], SNHG8 [ 17 ], SNHG12 [ 18 ], SNHG14 [ 19 ], SNHG15 [ 20 ], SNHG16 [ 21 ] that were previously reported to regulate inflammatory response. The experimental results revealed that SNHG8 showed the most significant upregulation in gouty mice compared to sham mice.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested a protective function for SNHG14 silencing against DN. SNHG1 knockdown inhibits HG‐induced ferroptosis of HK‐2 cells 18 ; SNHG5 knockdown alleviates podocyte injury 19 ; silencing of SNHG15 suppresses the inflammation in HG‐induced human glomerular mesangial cells 20 ; SNHG16 depletion inhibits the proliferation of mice mesangial cells 30 ; and SNHG17 knockdown reduces the apoptosis of podocytes. 31 Our study was the first to show the effects of the lncRNA SNHG family on DN via the regulation of fibrosis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Silencing SNHG15 attenuates DN progression in pediatric patients. 20 It is noteworthy that lncRNA SNHG14 is a newly found molecule mapping to 15q11.2 in humans 21 ; it exerts diverse functions in types of human diseases. 22 , 23 Additionally, studies have suggested the function of SNHG14 in renal injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most evidence in this attractive research area is based on adult [ 36 , 37 , 38 , 39 , 40 ] and in vitro studies [ 27 , 28 , 41 , 42 ], while similar pediatric data are still limited [ 43 , 44 , 45 , 46 , 47 ]. Due to the urgent need for early identification of DN and of the fragmentariness of data in the field in childhood, we attempted to provide a comprehensive pediatric overview on the challenging role of miRNAs in DN.…”
Section: Introductionmentioning
confidence: 99%